2009
DOI: 10.1177/0734242x09350059
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the preparation of wood-plastic composites from urban wastes generated in Merida, Mexico with potential applications as building materials

Abstract: A preliminary study on the use of wood and plastic wastes generated in Merida, Mexico to assess their potential for the development of building materials is reported. Composites based on recycled, high-density polyethylene (R-HDPE) loaded with wood particles were prepared. The R-HDPE was collected from Merida's Separation Plant, where it was sorted from other residues, either organic or inorganic. Composites based on virgin, high-density polyethylene (V-HDPE) were also prepared to assess the effect of the R-HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
(8 reference statements)
2
13
0
Order By: Relevance
“…Also because of recent need of novel application of materials from thermoplastic resins loaded with fillers in lignocelluloses fibers due to the added benefits that they provide to the materials in terms lightness, low cost, mechanical resistance etc. [2,34,35]. Consequently, this research may lead to emerging business as well as key sector that national, local governments and private organizations should assist.…”
Section: General Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also because of recent need of novel application of materials from thermoplastic resins loaded with fillers in lignocelluloses fibers due to the added benefits that they provide to the materials in terms lightness, low cost, mechanical resistance etc. [2,34,35]. Consequently, this research may lead to emerging business as well as key sector that national, local governments and private organizations should assist.…”
Section: General Conceptsmentioning
confidence: 99%
“…Recycling is being promoted worldwide as the way to address plastic items [38]. Many municipalities are establishing recycling programmes to battling with this problem at hand [35]. There are two significant reasons for the poor plastics recycling record: 1).…”
Section: Recycling Of Plastics Wastesmentioning
confidence: 99%
“…Focusing on the use of tree pruning as reinforcement has not been widely presented in the literature. There are some studies on obtaining composite materials from tree pruning (Hermawan et al 2009;Cruz-Estrada et al 2010;Sahin and Arslan 2013;Yeniocak et al 2014); however these articles are mainly devoted to the chemical properties of the fibers or the manufacturing of the boards. When the authors decided to study the use of orange tree pruning fibers (OPF) as PP reinforcement, they found only a few related studies.…”
Section: Introductionmentioning
confidence: 99%
“…dibutyl phthalate (DBP), dioctyl phthalate (DOP) [61], diisodecyl phthalate (DIDP) and di(2-ethylhexyl) phthalate (DEHP) [62,63]. There are also many bio-based plasticizers [64][65][66][67], in which the soybean oil and the epoxidizes soybean oil (ESBO) and the acetic acid ester (AAE) are the most common [68,69]. Cardanol is a natural resource with low cost and low toxicity [70].…”
Section: Materials and Equipmentmentioning
confidence: 99%